EDUCATION, POLITICAL CONNECTIONS, AND FIRM PERFORMANCE: EVIDENCE FROM GROWTH TRIANGLE COUNTRIES - Saputra, Irvan Pratama; Soewarno, Noorlailie (Universitas PGRI Madiun, 2024)
ABSTRACT This research aims to understand better how education influences overall company performance in the